Estudio de factibilidad para la creación de una operadora de turismo en deportes de aventura en el parque nacional Quilotoa provincia de Cotopaxi - Madrid Montalvo, Edgar Vinicio (2015)
The work presented then proposed a feasibility study for the creation of a tourism operator in adventure sports in the area of Laguna Quilotoa, located in the Ecological Reserve Illinizas in the province of Cotopaxi. For this we have developed an analysis based on the study of markets, technical study and financial study for determining the feasibility of the project to meet the needs of those who like to practice disciplines in sports in the open field and visit places that have not been tours and lack of market offerings. The research allowed to offer a service in adventure sports which allow national and foreign tourists travel to the reserve to enjoy the scenery and geography, retrieving their ancestral culture, respecting nature and contributing to the good life. By studying market has managed to establish the segment to who would be directed the project and the target application, the same that determines the quantization of the projection of potential customers of the service, as well as lay the foundations needed by the company to start operation. The technical study determines the optimal size of the demand for inputs, supplies and equipment needed to launch the project, financing and organization of the operator; and the technical parameters necessary for the proper functioning of the project is also set, taking advantage of all resources. The financial analysis shows that the implementation of the project is profitable.